2018
DOI: 10.5114/wiitm.2018.73528
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of malignancy in patients diagnosed with atypical ductal hyperplasia on vacuum-assisted core needle biopsy.

Abstract: IntroductionAtypical ductal hyperplasia (ADH) is a benign lesion, which due to the risk of coexisting cancer is classified as a lesion of uncertain malignant potential.AimTo identify clinical predictors of cancer underestimation in patients with ADH diagnosed after vacuum-assisted breast biopsy (VABB).Material and methodsBetween 2001 and 2016, a total of 3804 vacuum-assisted core needle biopsies were performed at the First Chair of General Surgery of the Jagiellonian University Medical College in Krakow, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The significant difference in the convergence of mammography and ultrasound results for BI-RADS scores of 4 and 5 in the literature and this study are probably due to the use of non-uniform, conservative and subjective criteria for qualifying breast tumours to particular BI-RADS categories, both in mammography and in ultrasound performed in the Population-based Breast Cancer Early Detection Screening Programme. A study by Hodorowicz-Zaniewska et al [7] showed no difference…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The significant difference in the convergence of mammography and ultrasound results for BI-RADS scores of 4 and 5 in the literature and this study are probably due to the use of non-uniform, conservative and subjective criteria for qualifying breast tumours to particular BI-RADS categories, both in mammography and in ultrasound performed in the Population-based Breast Cancer Early Detection Screening Programme. A study by Hodorowicz-Zaniewska et al [7] showed no difference…”
Section: Discussionmentioning
confidence: 88%
“…In the current study, breast cancer was significantly more frequently diagnosed in the biopsy material in women aged 56 69 (p<0.001). Hodorowicz-Zaniewska et al [7] also showed that the mean age of women with malignant breast lesions was 56.8±13.02. On the other hand, the results of the study by Dobruch-Sobczak [8] differed from the above -the mean age of patients with diagnosed breast cancer was lower and amounted to 55.07.…”
Section: Discussionmentioning
confidence: 91%
“… 2 Precancerous lesion (PL) refers to a lesion with a certain degree of atypical hyperplasia in histomorphology and the potential for canceration. 3 , 4 According to WHO, all kinds of lesions with more than 20% possibility of canceration belong to PL. 5 Breast precancerous lesions refer to a certain degree of morphological atypical hyperplasia of breast duct epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound (US) features such as margin, size of the lesions, and echogenicity features, are vital for the detection and discrimination of benign and malignant lesions ( 15 ), and also help in prediction of axillary lymph node metastasis in breast cancer ( 16 ). US has been widely used in imaging-guided breast CNB, especially in developing countries, with the advantage of real-time visualization, less expensive, not using ionizing radiation, and not limited to breast density ( 15 , 17 ). However, only a limited number of studies have investigated the use of US features for predicting the upgrade of ADH ( 18 ).…”
Section: Introductionmentioning
confidence: 99%